Analisis Penentuan Lokasi Tempat Penampungan Sementara (TPS) Sampah di Distrik Depapre Kabupaten Jayapura - Frans Magai; Alberth E S Abrauw; Alfred B Alfons (Journal of Innovative and Creativity, 2025)
This study analyzes the determination of temporary waste collection site (TPS) locations in Depapre District, Jayapura Regency, focusing on three villages: Tablanusu, Waiya, and Tablasupa. The research addresses the critical need for proper waste management infrastructure in a coastal tourism area that currently lacks adequate waste collection facilities. The study employed a descriptive survey method, utilizing both primary and secondary data through interviews with village heads and spatial analysis using Geographic Information System (GIS) buffering techniques. Population projections were calculated using arithmetic models, estimating growth from 1,368 residents in 2025 to 1,792 residents by 2034. Waste generation was calculated using SNI 19-3964-1995 standards at 0.08 kg/person/day and 2.5 liters/person/day. The research established five criteria for TPS site selection: road accessibility (buffer >100m), distance from settlements (<100m for accessibility), river proximity (>100m to prevent contamination), slope gradient (0-5% for optimal placement), and availability of vacant land (>10m²). GIS buffer analysis was applied to evaluate potential locations against these criteria. Results show that Waiya Village generates the highest daily waste volume at 470 kg (1,880 liters), followed by Tablasupa at 206 kg (823 liters), and Tablanusu at 179 kg (718 liters). The spatial analysis identified suitable locations in all three villages that meet the established criteria. The study recommends installing one 6m³ container-type TPS per village, with collection frequency of three times weekly using arm-roll trucks and three-wheeled vehicles for transportation. This research provides a scientific foundation for sustainable waste management planning in coastal tourism areas, contributing to environmental protection and supporting the tourism sector development in Depapre District